Decreased ZNF750 promotes angiogenesis in a paracrine manner via activating DANCR/miR-4707-3p/FOXC2 axis in esophageal squamous cell carcinoma - Bi, Yanghui (Cell Death Dis, 2020)
ZNF750 is one novel significantly mutated gene identified in esophageal squamous cell carcinoma (ESCC) using next-generation sequencing. However, its clinically relevant and potential mechanisms have remained elusive. Using genomic sequencing of 612 ESCC patients, we analyzed the associations of ZNF750 mutations with clinicopathologic features and its prognostic value. We further investigated the function and underlying mechanism of ZNF750 in angiogenesis. The results showed ZNF750 mutations/deletions are significantly associated with malignant progression and poor prognosis of ESCC patients. Decreased ZNF750 in ESCC cells induces enhanced angiogenesis of human umbilical vein endothelial cells (HUVECs) and human arterial endothelial cells (HAECs), and the effect may be indirectly mediated by FOXC2. RNA-seq and ChIP shows lncRNA DANCR is a direct downstream target of ZNF750. Furtherly, knockdown ZNF750 evokes DANCR expression, which prevents miR-4707-3p to interact with FOXC2 as a microRNA sponge in a ceRNA manner, leading to enhanced FOXC2 signaling and angiogenesis. In contrast, ZNF750 expression reverses the effect. Our study reveals a novel mechanism of ZNF750, highlights a significance of ZNF750 as a metastatic and prognostic biomarker, and offers potential therapeutic targets for ESCC patients harboring ZNF750 mutations.